Results of a Space-Surface Bistatic SAR Image Formation Algorithm - Antoniou, M.; Saini, R.; Cherniakov, M. (IEEE transactions on geoscience and remote sensing, 2007)
This paper reports progress in the development of an image formation algorithm suitable for stripmap space-surface bistatic synthetic aperture radar. A description of the proposed algorithm, which is a modification of the standard range-Doppler algorithm, is provided for the case when the transmitter and the receiver have parallel flight paths and unequal velocities. Both simulation and initial experimental results are presented to verify our analysis.